Variation of national and international guidelines on respiratory protection for health care professionals during the COVID-19 pandemic - Birgand, Gabriel; Mutters, Nico T.; Otter, Jonathan; Eichel, Vanessa; Lepelletier, Didier; Morgan, Daniel J.; Lucet, Jean-Christophe (JAMA network open, 2021)
This systematic review assesses variation in international and national guidelines on respiratory protection for health care professionals during the COVID-19 pandemic.